PENERAPAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SD NEGERI 010 SILIKUAN HULU KECAMATAN UKUI - Rubinem (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The problem in this research is the low results of students' mathematics learning in class II SD Negeri 010 Silikuan Hulu. Out of 34 students, only 10 students, or 29.41%, were resolved. Based on this, the researchers conducted classroom action research with the aim of improving learning outcomes through the application of mathematical models of quantum teaching learning. This study was conducted over two cycles, each cycle consisting of two meetings and one daily test. The instruments used were the observation sheet activities of teachers and students, and a math achievement test. The data collection technique used was the technique of observation and tests of learning outcomes. The study states that the application of the quantum model of teaching can enhance the activity of teachers and students and mathematics learning outcomes for second-grade students at SD Negeri 010 Silikuan Hulu. This is supported by: (a) the activities of teachers in each cycle increase. In the first meeting of the first cycle, activities for teachers received a score of 35, or 67.3%, placing it in the